The Effectiveness of Teaching Materials Based on Local Wisdom in the Takalar Region to Improve Literacy Capabilities of High School Students - Sri Ngabekti; Woro Sumarni; Sovi Junita Eviyanti (Postgraduate, University of Mataram, 2022)
The literacy ability of Indonesian students is still relatively low, there are several factors that cause it, one of which is an error in selecting learning resources, especially the teaching materials used by schools are not based on local wisdom and do not meet valid categories to measure literacy skills. For this reason, the development of module-based teaching materials is needed. local wisdom in supporting the achievement of competencies and goals in learning. This study aims to obtain a product through a process of testing the effectiveness to measure scientific, data and environmental literacy abilities. This research is development research (R&D) using 4-D type (Define, Design, Develop, Disseminate). The population of this study was class X students with a total of 141 consisting of small and large-scale tests. The results showed that the students' literacy skills were 71.86% (high), the results of the n-gain analysis for the experimental class were 0.70 and for the control class 0.55 (moderate). The results of the inferential analysis were obtained using a different test (t-test) showing that H0 was rejected and H1 was accepted, so it can be concluded that teaching materials based on local wisdom in the Takalar area provide a significant difference in increasing the literacy skills of class X students.